2010
DOI: 10.1007/s11244-010-9516-6
|View full text |Cite
|
Sign up to set email alerts
|

Site Structure Sensitivity Differences for Dissociation of Diatomic Molecules

Abstract: A review on the analysis based on our recent theoretical results on the site specific activation of CO, N 2 and NO on corrugated Ru surface is presented. We discuss the issues such as what should be the configuration of the active site for the optimum dissociation of the diatomic molecules?, How is the barrier dependent on the structure of the reaction path?, Whether the further steps involved in the reaction sequence dependent on the activation of the diatomic molecules?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…The large variation of CO dissociation barriers in magnitude of 1.43 eV (hcp) and 1.15 eV (fcc) suggests that CO dissociations are highly structure sensitive on both Ru phases. This is in good agreement with the result of diatomic molecules dissociation on transition-metal surfaces. ,, Considering typical aqueous-phase FTS reaction conditions (393–443 K), an increase of the dissociation barrier by 0.1 eV means a decrease of the corresponding rate constant by more than 1 order of magnitude. As a result, we focus below the structures with CO dissociation barrier falling in the window of 0.94–1.39 eV only, which contains 14 of 18 different surface structures (Figure ).…”
Section: Resultssupporting
confidence: 86%
“…The large variation of CO dissociation barriers in magnitude of 1.43 eV (hcp) and 1.15 eV (fcc) suggests that CO dissociations are highly structure sensitive on both Ru phases. This is in good agreement with the result of diatomic molecules dissociation on transition-metal surfaces. ,, Considering typical aqueous-phase FTS reaction conditions (393–443 K), an increase of the dissociation barrier by 0.1 eV means a decrease of the corresponding rate constant by more than 1 order of magnitude. As a result, we focus below the structures with CO dissociation barrier falling in the window of 0.94–1.39 eV only, which contains 14 of 18 different surface structures (Figure ).…”
Section: Resultssupporting
confidence: 86%
“…Even lower barriers are found for direct CO dissociation on the Co(101̅0)B surface (B refers to the specific surface cut)where the activation barrier is only 68 kJ/mol, whereas the overall barrier for the hydroxycarbene (HCO) mechanism is 105 kJ/mol on the same surface. Other computational studies also indicate that the carbene mechanism is indeed the preferred route on stepped and corrugated metal surfaces such as ruthenium, , rhodium, and cobalt . An ideal active site for FTS should not only have low barriers for CO dissociation but also allow for a propagation cycle to take place that can sustain itself.…”
Section: Introductionmentioning
confidence: 99%
“…It was proposed that the cleavage of either the C–O bond of the molecule itself (carbide mechanism) or its partially hydrogenated intermediates (via H-assisted mechanism) is responsible for the formation of these important precursor species on Ru, with the morphology of the surface dictating which pathway dominates . On stepped and corrugated surfaces, for example, temperature desorption spectroscopy (TDS), high-resolution electron energy loss spectroscopy (HREELS), infrared reflection–absorption spectroscopy (IRAS), and low-energy electron diffraction (LEED) studies indicate that the carbide mechanism was preferred with direct dissociation occurring in the temperature range of 300–500 K. Subsequent density functional theory (DFT) studies based on model surfaces containing under-coordinated sites, such as steps, revealed that the molecule was tilted with both carbon and oxygen essentially interacting with metal atoms. The activation of the C–O bond resulting from the enhanced interaction with the surface was thought to be responsible for the low barrier dissociation of the molecule.…”
Section: Introductionmentioning
confidence: 99%